Association of Dynamic Changes in the CD4 T-Cell Transcriptome With Disease Severity During Primary Respiratory Syncytial Virus Infection in Young Infants. (17th August 2017) - Mariani, Thomas J; Qiu, Xing; Chu, ChinYi; Wang, Lu; Thakar, Juilee; Holden-Wiltse, Jeanne; Corbett, Anthony; Topham, David J; Falsey, Ann R; Caserta, Mary T; Walsh, Edward E
Abstract : CD4 T-cell transcriptomic results reveal significant changes associated with disease severity in primary respiratory syncytial virus infection, with evidence of Th2 skewing, and provide insight into early T-cell responses associated with disease severity. Abstract: Background: Nearly all children are infected with respiratory syncytial virus (RSV) within the first 2 years of life, with a minority developing severe disease (1%–3% hospitalized). We hypothesized that an assessment of the adaptive immune system, using CD4 + T-lymphocyte transcriptomics, would identify gene expression correlates of disease severity. Methods: Infants infected with RSV representing extremes of clinical severity were studied. Mild illness (n = 23) was defined as a respiratory rate (RR) < 55 and room air oxygen saturation (SaO2 ) ≥ 97%, and severe illness (n = 23) was defined as RR ≥ 65 and SaO2 ≤ 92%. RNA from fresh, sort-purified CD4 + T cells was assessed by RNA sequencing. Results: Gestational age, age at illness onset, exposure to environmental tobacco smoke, bacterial colonization, and breastfeeding were associated (adjusted P < .05) with disease severity. RNA sequencing analysis reliably measured approximately 60% of the genome. Severity of RSV illness had the greatest effect size upon CD4 T-cell gene expression. Pathway analysis identified correlates of severity, including JAK/STAT, prolactin, and interleukin 9 signaling. We also identified genes and pathways associated with timing of symptoms and RSV group (A/B). Conclusions: These data suggest fundamental changes in adaptive immune cell phenotypes may be associated with RSV clinical severity.